2020
DOI: 10.3238/arztebl.2020.0709
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reported Psychosocial Stress in Parents With Small Children

Abstract: sychosocial stress, especially adverse childhood experiences, is disproportionately likely to influence child development in negative ways and often leads to risky health behavior, such as substance abuse, increased burden of disease and increased healthcare costs (1). In Germany, a retrospective survey showed that difficulties in the parental home as well as violence and deprivation experiences were associated with an increased likelihood of depression, anxiety, physical aggression, and low life satisfaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
0
6
0
3
Order By: Relevance
“…Parents are constantly having to take on new responsibilities, master different skills, and navigate issues that arise as their child grows—all of which require confidence and an ability to manage stress. Many studies document the stressors of parenthood and how a lack of parental support can compound this stress while access to a supportive network can lead to better parenting practices and child development (Lorenz et al, 2020 ; McConnell et al, 2011 ; Parkes et al, 2015 ; Taylor et al, 2015 ). But there is surprisingly little research on how social support might aid the toilet training process.…”
Section: Introductionmentioning
confidence: 99%
“…Parents are constantly having to take on new responsibilities, master different skills, and navigate issues that arise as their child grows—all of which require confidence and an ability to manage stress. Many studies document the stressors of parenthood and how a lack of parental support can compound this stress while access to a supportive network can lead to better parenting practices and child development (Lorenz et al, 2020 ; McConnell et al, 2011 ; Parkes et al, 2015 ; Taylor et al, 2015 ). But there is surprisingly little research on how social support might aid the toilet training process.…”
Section: Introductionmentioning
confidence: 99%
“…Central for answering the research questions is to assess the risk factors and perceived psychosocial burden of the families. We therefore apply an additive index and count up the risk factors asked for, as is commonly used in research and previous studies [ 1 , 20 , 21 ]. The index comprises six domains, namely the (a) family background, (b) parent’s individual preconditions for dealing with care challenges, (c) parent’s psychological health, (d) difficulties during pregnancy and in interaction with the child, (e) special care challenges regarding the child, and (f) problematical caring behavior.…”
Section: Methodsmentioning
confidence: 99%
“…Newborns and infants are specifically vulnerable as the perinatal period and the first year of life are critical phases for the cognitive, physical, and emotional development (DeSocio, 2018). A German representative study revealed that around 40% of families participating in the child development checks at paediatric practices reported three or more psychosocial stress areas, adverse biographical, prenatal, or perinatal characteristics (Lorenz, Ulrich, Sann, et al, 2020).…”
Section: Palabras Clave: Estrés Prenatal Estré Prenatal Revisión Coop...mentioning
confidence: 99%
“…Thus, a personal anamnesis by a qualified person is necessary to discuss risk factors and subjective distress experienced by families as well as to identify the specific needs (Metzner & Pawils, 2021). Since parental challenges may differ during a child's first year of life, a continuous monitoring of the psychosocial situation during pregnancy and in the first year of life is important (Lorenz, Ulrich, Sann, et al, 2020). At present, the regular outpatient healthcare in Germany is supposed to include a social anamnesis during prenatal care check-ups and the well-child-visits.…”
Section: Palabras Clave: Estrés Prenatal Estré Prenatal Revisión Coop...mentioning
confidence: 99%